Does resveratrol retain its antioxidative properties in wine? Redox behaviour of resveratrol in the presence of Cu(II) and tebuconazole - Jaklová Dytrtová, Jana; Straka, Michal; Bělonožníková, Kateřina; Jakl, Michal; Ryšlavá, Helena (Food chemistry, 2018)
Resveratrol is antioxidant naturally occurring in wine grapes. It is thought to have a preventive biological activity against number of diseases. However, it has been recently shown that in the presence of metal ions, such as Cu2+, resveratrol forms oxidative radicals. Cu2+ is usually present in wine due to former usage of bluestone in vineyards. Fungicide tebuconazole has substituted bluestone and is presently one of the most widely used agrochemicals in wine industry; wine thus may contain traces of tebuconazole. Here, we study the ternary system of resveratrol, Cu2+, and tebuconazole experimentally and theoretically (using mass spectrometry, antioxidant capacity assay and quantum-chemical calculations) to model the redox behaviour of resveratrol in wine. We show that tebuconazole prevents formation of oxidative resveratrol radicals (induced by Cu2+ reaction with resveratrol) via preferential Cu2+ capture and protection of the binding sites of resveratrol. This positive effect of tebuconazole has not been observed before.
Keywords: Triazoles; DFT; víno; Resveratrol; Antioxidants; Copper; FRAP; resveratrol; měď; Mass Spectrometry; Oxidation-Reduction; Polyphenols; antioxidancia; Wine; průmyslové fungicidy; triazoly; Antioxidant capacity; Fungicides, Industrial; stilbeny; oxidace-redukce; Stilbenes; hmotnostní spektrometrie; ESI-MS